Basic researchDown-regulation of intrahepatic CD16+ and CD56+ immune cells in chronic Hepatitis C virus infection and HCV-related hepatocellular carcinoma - El Bassiouny, Azza; El-Hassan, Samah Abo; Moussa, Mona; El-Ahwany, Eman; Helal, Eman; Taha, Alaa; Helmy, Ahmed-Hazem; Kamel, Manal; El-Bassiouni, Nora (Archives of Medical Science, 2009)
Introduction: The intrahepatic pool of natural killer (NK) and lymphocytes with NK receptors (NKRs) is thought to play a key role in determining whether host immune responses to hepatitis C virus (HCV) infection result in viral clearance or disease progression. Material and methods: Liver biopsies were taken from 116 patients with chronic hepatitis C (CHC) infection, 44 of whom had liver cirrhosis (LC), and 36 patients had hepatocellular carcinoma (HCC). Twenty histologically normal livers served as controls. Tissue sections were stained with CD16 and CD56 monoclonal antibodies by avidin-biotin peroxidase complex method and were semi-quantitatively evaluated. Results: The CD16 and CD56 immunoreactivity on intrahepatic NK cells and lymphocytes was significantly decreased in patients with CHC (34.8 ±1.9, 4.3 ±0.4, respectively), LC (22.4 ±0.3, 1.5 ±0.6, respectively) and HCC (11.5 ±1.1, 0.6 ±0.3, respectively) compared to controls (p < 0.05) with sequence order. Moreover, NK cells and lymphocytes positive for CD16 and CD56 in the liver of patients with high METAVIR scores for chronic hepatitis were significantly reduced compared to patients with low score (p < 0.01). The CD16+ Kupffer cells were, also, reduced in CHC compared to controls (p < 0.01), and the reduction was more pronounced with the progression of the disease. Conclusions: These data show that CHC is associated with defects in NK cells and CD56+ lymphocytes that correlate with the degree of inflammatory activity and stage of hepatic fibrosis. The reduced CD16+ Kupffer cells in chronic HCV infection and HCC stress the important role of these cells in antiviral and antitumor immunity.